2021
DOI: 10.35467/sdq/135580
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue "Non-military aspects of security in the changing international order"

Abstract: S afety is the fundamental value in the system of the needs of individuals, states, groups, and social systems. With reference to an existential dimension of a given subject's being, it means the certainty of its survival and existence. It can be considered both as a factor determining the state of a subject at a specified time or over a longer period of time (the processual dimension) and, in the latter, it refers to the durability of the subject's existence as well as its ability to survive and develop in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This identified the knowledge base of an informed citizen, ready to pursue their social, economic and political needs [6]. Although no direct reference was made to the institutions of the European Union or to the organisation itself [23,27], it can be indicated that the preferences of the young Community citizens surveyed today portend certain behaviour in the future. In the context of the European Green Deal, it is assumed that the current high standard of living of Europeans will be improved by meeting life, environmental, individual, group and social needs [28].…”
Section: Methodsmentioning
confidence: 99%
“…This identified the knowledge base of an informed citizen, ready to pursue their social, economic and political needs [6]. Although no direct reference was made to the institutions of the European Union or to the organisation itself [23,27], it can be indicated that the preferences of the young Community citizens surveyed today portend certain behaviour in the future. In the context of the European Green Deal, it is assumed that the current high standard of living of Europeans will be improved by meeting life, environmental, individual, group and social needs [28].…”
Section: Methodsmentioning
confidence: 99%
“…In opposition to the previous theory, the modern one recognizes security from a number of non-military conflicts, tensions, and crises (Ivančík, 2021). According to Lizak, Zajączkowski, Kołodziejczak (2021), modern civilization faces the increasing role of the scientific and technical aspects and they build the dynamics of social and economic changes encourage the introduction of innovations to meet human needs. This translates security in a much broader sense which occurs on the individual, state and international levels Security is one of the characteristics and criteria of functioning of all the social, economic, technical, ecological, and other systems.…”
Section: Literature Review/theoretical Overviewmentioning
confidence: 99%
“…Figure 2 shows the nature of security interpretation in philosophical literature. The first group related to explanation of security as state of protection, absence of threats, specific activity aimed at satisfaction of needs of social system, combination of factors that provide secure development of state, system where interests of individuals, society and state are interrelated and complement each other (Lizak, Zajączkowski, Kołodziejczak, 2021, Şengöz, 2022, Kupiecki, 2022, Pankowska, 2019.…”
Section: Literature Review/theoretical Overviewmentioning
confidence: 99%